The Economic Returns to Graduating with Honors - Evidence from Law Graduates - Mathias Schumann; Ronny Freier; Thomas Siedler (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper studies the causal effects of graduating from university with an honors degree on subsequent labor market outcomes. While a rich body of literature has focused on estimating returns to human capital, few studies have analyzed returns at the very top of the education distribution. We highlight the importance of honors degrees for future labor market success in the context of German law graduates. Using a difference-in-differences research design combined with entropy balancing, we find that students of law who passed the state bar exam with an honors degree receive a significant earnings premium (about 14 percent), are more likely to work in public service (about 16 percentage points), are less likely to be self-employed (seven percentage points) and are more often engaged in Ph.D. studies (about 20 percentage points).
Keywords: J01; J31; J44; 330